Binding and internalization of the Helicobacter pylori vacuolating cytotoxin by epithelial cells. - Garner, J A (1996)
Many Helicobacter pylori strains produce a cytotoxin (VacA) that induces vacuolation in epithelial cells. In this study, binding and internalization of the cytotoxin by HeLa or AGS (human gastric adenocarcinoma) cells were characterized by indirect fluorescence microscopy. Cells incubated with the cytotoxin at 4 degrees C displayed a uniform fluorescent plasma membrane signal. Preincubation of the cytotoxin with either rabbit antiserum to approximately 90-kDa H. pylori VacA or sera from H. pylori-infected persons inhibited its binding to cells and blocked its capacity to induce cytoplasmic vacuolation. Recombinant VacA fragments (approximately 34 and approximately 58 kDa), corresponding to two proteolytic cleavage products of approximately 90-kDa VacA, each bound to the plasma membrane of HeLa cells. Antiserum reactive with the approximately 58-kDa VacA fragment inhibited the binding of native H. pylori cytotoxin to cells and inhibited cytotoxin activity, whereas antiserum to the approximately 34-kDa fragment had no effect. When incubated with cells at 37 degrees C for > or = 3 h, the H. pylori cytotoxin localized intracellularly in a perinuclear location but did not localize within cytotoxin-induced vacuoles. When cells with previously bound cytotoxin were incubated with anticytotoxin serum at 4 degrees C and then shifted to 37 degrees C, vacuolation was completely inhibited. Bound cytotoxin became inaccessible to the neutralizing effects of antiserum after 60 to 120 min of incubation with cells at 37 degrees C. These data suggest a model in which (i) VacA binds to cells primarily via amino acid sequences in its 58-kDa fragment, (ii) VacA internalization occurs slowly in a temperature-dependent process, and (iii) VacA interacts with an intracellular target.